Alanine Aminotransferase Homologs Catalyze the Glutamate:Glyoxylate Aminotransferase Reaction in Peroxisomes of Arabidopsis - Liepman, Aaron H. (American Society of Plant Biologists, 2003)
Plant peroxisomal glyoxylate aminotransferases play central roles within the photorespiratory pathway. Genes encoding glyoxylate aminotransferases have been isolated from several animals and microbes, but only recently have plant homologs been identified. Three Arabidopsis homologs of alanine (Ala):glyoxylate aminotransferase 2 (AGT2) contain a putative type 1 peroxisomal targeting signal (PTS1), but the metabolic significance of these AGT2 homologs is unknown. GGT1 and GGT2 are Ala aminotransferase (AlaAT) homologs from Arabidopsis that represent another type of glyoxylate aminotransferase. These proteins are class I aminotransferases, each containing a putative PTS1. GGT1 and GGT2 are members of a small family of AlaATs in Arabidopsis. When expressed as recombinant proteins in Escherichia coli, GGT1 and GGT2 displayed biochemical characteristics very similar to one another, and to the Arabidopsis protein purified from leaves. Four aminotransferase activities were specifically associated with GGT1 and GGT2, using the substrate pairs glutamate (Glu):glyoxylate, Ala:glyoxylate, Glu:pyruvate, and Ala:2-oxoglutarate. GGT1 and GGT2 may have partially redundant functions; transcripts of both genes were detected in many of the same tissues. Although Glu:glyoxylate aminotransferase (GGT) activity has been observed in several locations in different plants and algae, including the cytoplasm and mitochondria, our subcellular fractionation data indicate that GGT activity was exclusively peroxisomal in Arabidopsis. Thus, glyoxylate aminotransferase reactions in plant peroxisomes appear to be catalyzed by at least two distinct types of aminotransferases: an AGT1 homolog with serine:glyoxylate aminotransferase activity (A.H. Liepman, L.J. Olsen [2001] Plant J 25: 487–498), and a pair of closely related, potentially redundant AlaAT homologs with GGT activity.